Hyperkeratotic erythema multiforme variant in 17 dogs. Issue 2 (12th December 2022) - Banovic, Frane; Olivry, Thierry; Artlet, Barbara; Rothstein, Emily; Beco, Luc; Linek, Monika; Zabel, Sonja; Peters‐Kennedy, Jeanine; Welle, Monika; Wilkes, Rebecca; Austel, Michaela; Linder, Keith
Abstract: Background: A new canine subgroup defined as 'old‐dog' or 'hyperkeratotic' erythema multiforme (HKEM) with marked hyperkeratosis and parakeratosis has been proposed without any detailed description of larger case series. Objectives: We report herein the signalment, clinical signs, treatment outcome, and histopathological and immunological findings in 17 dogs with HKEM. Animals: Inclusion criteria were the presence of (i) scaly skin lesions with or without crusting; and (ii) microscopic lesions typical of EM (i.e. a panepidermal cytotoxic lymphocytic dermatitis with or without basal keratinocyte apoptosis); and (iii) microscopic ortho‐ and/or parakeratotic hyperkeratosis affecting the interfollicular epidermis. Materials and Methods: Clinical questionnaires and skin biopsies were reviewed. Polymerase chain reactions for epidermotropic viruses and direct immunofluorescence were performed. Results: Various breeds were affected with an over‐representation of males in their mid‐to‐late adulthood (median age 9 years). Generalised skin lesions included multifocal‐to‐coalescing, linear and annular macules and plaques with erythema and adherent firm crusting. Microscopic lesions were specific for EM and featured prominent superficial epidermal apoptosis with lymphocytic satellitosis and parakeratosis. No drug triggers were identified. Polymerase chain reactions for canine herpesvirus polymerase gene, canine parvovirus and canine distemper virus were negative in all HKEM and canine erosive EM (15 dogs) biopsies. Lesions failed to respond to oral and/or topical antimicrobials. Complete remission of signs was achieved in 9 of 17 dogs (53%) using immunosuppressive regimens. Conclusions and Clinical Relevance: Hyperkeratotic erythema multiforme (HKEM) is a chronic, persistent and clinically distinctive erythema multiforme (EM) variant that differs from 'classic' vesiculobullous erosive‐to‐ulcerative EM in dogs. Abstract : Background – A new canine subgroup defined as 'old‐dog' or 'hyperkeratotic' erythema multiforme (HKEM) with marked hyperkeratosis and parakeratosis has been reported without a previous description of larger case series. Objectives – We report herein the signalment, clinical signs, treatment outcome, and histopathological and immunological findings in 17 dogs with HKEM. Conclusions and Clinical Relevance – HKEM is a chronic, persistent and clinically distinctive Erythema multiforme (EM) variant that differs from 'classic' vesiculobullous erosive‐to‐ulcerative EM in dogs. Résumé: Contexte: De nouveaux sous‐groupes canins définis comme des érythèmes polymorphes « vieux chiens » et « hyperkératosiques » (HKEM) avec une hyperkératose et une parakératose marquées ont été proposés sans aucune description détaillée de séries de cas plus importantes. Objectifs: Nous rapportons ici le signalement, les signes cliniques, les résultats du traitement et les résultats histopathologiques et immunologiques chez 17 chiens atteints de HKEM. Animaux: Les critères d'inclusion étaient la présence de : (i) lésions cutanées squameuses avec ou sans croûtes; et (ii) des lésions microscopiques typiques de l'EM (c'est‐à‐dire une dermatite lymphocytaire cytotoxique panépidermique avec ou sans apoptose basale des kératinocytes); et (iii) une hyperkératose microscopique ortho‐ et/ou parakératosique affectant l'épiderme interfolliculaire. Matériels et méthodes: Des questionnaires cliniques et des biopsies cutanées ont été examinés. Des réactions en chaîne par polymérase pour les virus épidermotropes et une immunofluorescence directe ont été réalisées. Résultats: Diverses races étaient touchées avec une surreprésentation des mâles dans leur âge moyen à tardif (âge médian neuf ans). Les lésions cutanées généralisées comprenaient des macules et des plaques multifocales à coalescentes, linéaires et annulaires avec un érythème et des croûtes fermes adhérentes. Les lésions microscopiques étaient spécifiques de l'EM et comportaient une apoptose épidermique superficielle proéminente avec une satellitose lymphocytaire et une parakératose. Aucun déclencheur médicamenteux n'a été identifié. Les réactions en chaîne de la polymérase pour le gène de la polymérase de l'herpèsvirus canin, le parvovirus canin et le virus de la maladie de Carré étaient négatives dans toutes les biopsies HKEM et EM érosive canine (15 chiens). Les lésions n'ont pas répondu aux antimicrobiens oraux et/ou topiques. Une rémission complète des signes a été obtenue chez neuf des 17 chiens (53 %) en utilisant des traitements immunosuppresseurs. Conclusions et pertinence clinique: HKEM est une variante EM chronique, persistante et cliniquement distincte qui diffère de l'EM vésiculobulleuse « classique » érosive à ulcérative chez le chien. Resumen: Introducción: Se han propuesto nuevos subgrupos caninos de eritema multiforme definidos como "de perro viejo" e "hiperqueratósico" (HKEM) con hiperqueratosis y paraqueratosis marcadas sin ninguna descripción detallada de series de casos más grandes. Objetivos: En este documento describimos la presentación, los signos clínicos, el resultado del tratamiento y los hallazgos histopatológicos e inmunológicos en 17 perros con HKEM. Animales: Los criterios de inclusión fueron la presencia de: (i) lesiones cutáneas escamosas con o sin formación de costras; y (ii) lesiones microscópicas típicas de EM (es decir, una dermatitis linfocítica citotóxica panepidérmica con o sin apoptosis de queratinocitos basales); y (iii) hiperqueratosis microscópica orto y/o paraqueratósica que afecta la epidermis interfolicular. Materiales y Métodos: Se revisaron cuestionarios clínicos y biopsias de piel. Se realizaron reacciones en cadena de la polimerasa (PCR) para virus epidermotrópicos e inmunofluorescencia directa. Resultados: Varias razas se vieron afectadas con una sobrerrepresentación de machos en su edad adulta media o tardía (edad media de nueve años). Las lesiones cutáneas generalizadas incluyeron máculas y placas lineales y anulares, multifocales a coalescentes, con eritema y formación de costras firmes y adherentes. Las lesiones microscópicas fueron específicas para EM y presentaban apoptosis epidérmica superficial prominente con satelitosis linfocítica y paraqueratosis. No se identificaron desencadenantes farmacológicosmm. Las reacciones en cadena de la polimerasa para el gen de la polimerasa del herpesvirus canino, el parvovirus canino y el virus del moquillo canino fueron negativas en todas las biopsias HKEM y EM erosiva canina (15 perros). Las lesiones no respondieron a los antimicrobianos orales y/o tópicos. Se logró la remisión completa de los signos en nueve de 17 perros (53 %) usando regímenes inmunosupresores. Conclusiones y relevancia clínica: HKEM es una variante de EM crónica, persistente y clínicamente distintiva que difiere de la EM vesiculoampollosa "clásica" erosiva a ulcerosa en perros. Zusammenfassung: Hintergrund: Neue canine Untergruppen, die definiert wurden als „alter‐Hund" und „hyperkeratotisches Erythema multiforme (HKEM) mit deutlicher Hyperkeratose und Parakeratose wurden ohne detaillierte Beschreibung größerer Fallserien vorgeschlagen. Ziele: Hierin beschreiben wir das Signalement, die klinischen Zeichen, den Behandlungsausgang, und die histopathologischen und immunologischen Befunde bei 17 Hunden mit HKEM. Tiere: Inklusionskriterien waren das Vorhandensein von: (i) schuppigen Hautveränderungen mit oder ohne Krustenbildung; und (ii) mikroskopischen Läsionen von EM (i.e. eine panepidermale zytotoxische lymphozytäre Dermatitis mit und ohne Apoptose der basalen Keratinozyten); und (iii) mikroskopischer ortho‐ und/oder parakeratotischer Hyperkeratose, die die interfollikuläre Epidermis betrifft. Materialien und Methoden: Klinische Fragebögen und Hautbiopsien wurden reviewed. Es wurden Polymerasekettenreaktionen auf epidermotropisches Virus und direkte Immunfluoreszenz durchgeführt. Ergebnisse: Es waren verschiedene Rassen betroffen, wobei männliche Tiere in mittlerem bis späterem Erwachsenenalter (das mediane Alter betrug neun Jahre) überrepräsentiert waren. Generalisierte Hautveränderungen bestanden aus multifokalen‐bis koaleszierenden, linearen und annularen Maculae und Plaques mit Erythem und anhaftenden festen Krusten. Die mikroskopischen Veränderungen waren spezifisch für EM und zeigten eine prominente superfizielle epidermale Apoptose mit lymphzytärer Satellitose und Parakeratose. Es wurden keine eindeutigen Auslöser identifiziert. Polymerasekettenreaktionen auf canines Herpesvirus Polymerase Gen, canines Parvovirus und canines Staupevirus waren in allen HKEM und den caninen erosiven EM‐Biopsien (15 Hunde) negativ. Die Veränderungen reagierten nicht auf orale und/oder topische Antibiotika. Eine komplette Remission der Zeichen wurde bei neun von 17 Hunden (53%) mittels Immunsupressiva erzielt. Schlussfolgerungen und klinische Bedeutung: HKEM ist eine chronische, persistierende und klinisch eindeutige EM‐Variante, die sich von der „klassischen" vesikulobullösen erosiv‐bis‐ulzerativen EM der Hunde unterscheidet. 要約: 背景: 犬の多形紅斑には、「老犬型」「過角化型(HKEM)」という新しいサブグループが提案されているが、大規模な症例に関する詳細な記述はない。 目的: 本研究の目的は、過角化型多形紅斑を発症した17頭の犬について、シグナルメント、臨床症状、治療成績、病理組織学的および免疫学的所見を報告することであった。 対象動物: (1) 痂皮を伴うか否かの鱗屑性皮膚病変、(2) EMに典型的な顕微鏡的病変(すなわち、基底細胞のアポトーシスを伴うか否かの汎上皮細胞障害性リンパ球性皮膚炎)、(3) 毛包間表皮を冒す顕微鏡的正角化性および/または不全角化性角化亢進が認められることを登録条件とした。 材料と方法: 臨床アンケートおよび皮膚生検のレビューを行った。上皮向性ウイルスに対するポリメラーゼ連鎖反応および直接免疫蛍光検査を行った。 結果: 様々な犬種が罹患し、成犬中期から後期(中央値9歳)の雄に過剰発現していた。全身の皮膚病変は、紅斑および付着性の固い痂皮を伴う、多巣性〜癒合性の線状および環状の斑およびプラークを含んでいた。顕微鏡所見では、EMに特異的で、リンパ球性衛生現象を伴う表皮表面のアポトーシスおよび錯角化が顕著であった。薬物による誘発は確認されなかった。犬ヘルペスウイルスポリメラーゼ遺伝子、犬パルボウイルス、犬ジステンパーウイルスに対するポリメラーゼ連鎖反応は、HKEMおよび犬びらん性EM(15頭)のすべての生検で陰性であった。病変は経口および外用抗菌薬に反応しなかった。免疫抑制療法により17頭中9頭(53%)で症状の完全寛解が得られた。 結論と臨床的意義: HKEMは，"古典的 "な小水疱性びらん‐潰瘍性EMとは異なる、慢性で持続的で臨床的に特徴的なEMの一形態である。 摘要: 背景: 提出了定义为"老年犬"和"角化过度"多形红斑 (HKEM) 伴明显角化过度和角化不全的新亚组，未对更大的犬病例系列进行任何详细描述。 目的: 我们在此报告了17只HKEM犬的病征、临床症状、治疗结果以及组织病理学和免疫学结果。 动物: 入选标准为存在:(i) 皮屑性病变伴或不伴结痂；和 (ii)EM 的典型显微镜下病变(即全表皮细胞毒性淋巴细胞性皮炎伴或不伴基底角质细胞凋亡)；和 (iii) 影响毛囊间表皮的显微镜下角化过度和/或角化不全。 材料和方法: 审查临床问卷和皮肤活检。对亲表皮病毒进行聚合酶链反应和直接免疫荧光检测。 结果: 不同品种发病，成年中后期(中位年龄9岁)公犬比例过高。全身性皮肤病变包括多灶性至融合、线性和环形的斑疹和斑块，伴红斑和粘连性结痂。显微镜下具有EM特异性病变，以突出的浅表表皮凋亡，伴淋巴细胞卫星现象和角化不全为特征。未发现药物触发因素。犬疱疹病毒聚合酶基因、犬细小病毒和犬瘟热病毒的聚合酶链反应在所有 HKEM 和犬糜烂性EM(15只犬)活检中均为阴性。病变经口服和(或)外用抗菌药治疗无效。使用免疫抑制方案时，9/17只犬 (53%) 的症状完全缓解。 结论和临床相关性: HKEM是一种慢性、持续性和临床上独特的 EM 变体，不同于犬的"经典"水疱大疱性糜烂至溃疡性EM。 Resumo: Contexto: Novos subgrupos caninos definidos como eritema multiforme do "cão idoso" e "hiperqueratótico" (HKEM) apresentando hiperqueratose e paraqueratose acentuadas têm sido propostos sem qualquer descrição detalhada em uma série de casos maior. Objetivos: Nós relatamos aqui os sinais clínicos, resposta ao tratamento, e achados histopatológicos imunológicos em 17 cães com (HKEM). Animais: Os critérios de inclusão foram a presença de: (i) lesões cutâneas descamativas com ou sem crostas;(ii) lesões microscópicas típicas EM (exemplo: dermatite citotóxica linfocítica panepidermal com ou sem apoptose dos queratinócitos da camada basal); e (iii) hiperqueratose orto e/ou paraqueratótica afetando a epidermie interfolicular. Materiais e métodos: Questionários clínicos e biópsias cutâneas foram revisados. Realizou‐se PCR de vírus epidermotrópicos. Resultados: Diversas raças foram afetadas e houve uma super‐representação de machos de meia idade (idade média de nove anos). As lesões cutâneas generalizadas incluíram máculas e placas multifocais a coalescentes, lineares e anulares com eritema e crostas firmes aderentes. As lesões microscópicas eram específicas para EM e apresentavam apoptose epidérmica superficial proeminente com satelitose linfocítica e paraqueratose. Nenhum medicamento foi identificado como agente incitane. As reações em cadeia da polimerase para o gene da polimerase do herpesvírus canino, parvovírus canino e vírus da cinomose foram negativas em todas as biópsias HKEM e EM erosiva canina (15 cães). As lesões não responderam aos antimicrobianos orais e/ou tópicos. A remissão completa dos sinais ocorreu em nove dos 17 cães (53%) usando imunossupressores. Conclusões e relevância clínica: HKEM é uma variante crônica, persistente e clinicamente distinta do EM que difere do EM vesiculobolhoso erosivo‐ulcerativo "clássico" em cães.